1982
DOI: 10.1111/j.1365-2362.1982.tb00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte deformability in dialysed and non‐dialysed uraemic patients

Abstract: In thirty-one uraemic patients, fourteen on conservative treatment and seventeen on long-term haemodialysis, erythrocyte deformability, measured as filtration half-time in a paper filtration experiment, was studied. The two groups were comparable concerning age, sex and kidney disease. Although the mean filtration half-time for erythrocyte suspensions was normal in non-dialysed patients there was a positive linear correlation (P less than 0.01) between serum creatinine and filtration half-time in this group. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…This observation is in agreement with earlier findings [23]. From reports [10][11][12] that RBC deformability is significantly impaired in uremia, one might expect WBV to become abnormally elevated following improvement of anemia; however, our results indicate that both PV and WBV (for all levels of hematocrit stud ied at high and low rates of shear) fall within the ranges derived from our normal reference group. These findings suggest that if RBC deformability is in fact impaired in our patients, the degree of impairment is not sufficient to cause an inappropriate rise in blood viscosity, following treatment of anemia with rhEPO.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This observation is in agreement with earlier findings [23]. From reports [10][11][12] that RBC deformability is significantly impaired in uremia, one might expect WBV to become abnormally elevated following improvement of anemia; however, our results indicate that both PV and WBV (for all levels of hematocrit stud ied at high and low rates of shear) fall within the ranges derived from our normal reference group. These findings suggest that if RBC deformability is in fact impaired in our patients, the degree of impairment is not sufficient to cause an inappropriate rise in blood viscosity, following treatment of anemia with rhEPO.…”
Section: Discussionsupporting
confidence: 66%
“…Using a microfiltration technique, Docci et al [10] and others [11,12] observed that red blood cell (RBC) deformability is markedly reduced in patients with renal fail ure. Rigid RBCs tend to resist shear deformation; there fore, cell-to-cell viscous interaction increases.…”
Section: Introductionmentioning
confidence: 99%
“…Microangiopathy of the subepidermal capillaries [21,22] and reduced erythrocyte deformability [23,24] could also impair maximal skin blood How.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia in C R F has been associated with decreased R B C deformability [9], increased magnesium content [10] and potassium content [II], We described an association between R B C rigidity and increased calcium content but found no correlation between calcium content or defor mability and the degree o f anemia [2]. These studies do not show that changes in cation content are directly responsible for R B C dysfunction in uremia.…”
mentioning
confidence: 45%